Long-term analysis of the resistance development in HIV-1 positive patients treated with protease and reverse transcriptase inhibitors: correlation of the genotype and disease progression - Václavíková, J; Weber, J; Machala, L; Reinis, M; Linka, M; Brůcková, M; Vandasová, J; Stanková, M; Konvalinka, J (Acta virologica, 2005)
In this study, 27 HIV-1-positive patients on long-term highly active antiretroviral therapy (HAART) in the Czech Republic were followed for a period of up to 7 years. Variability of the HIV-1 protease (PR) sequence common in the Czech Republic was observed. Under the pressure of inhibitors of protease (PRIs) and reverse transcriptase (RTIs) mutations in PR were detected. Development of resistance to PRIs was followed by a decrease in CD4 count and increase in viral load. The dynamics of viral load closely corresponded to the accumulation of specific primary mutations in PR and RT. Out of 27 patients 18 developed resistance to PRIs and the prolonged therapy led to the accumulation of a higher number of amino acid changes associated with the resistance and, consequently, cross-resistance to several PRIs was observed. These multi-resistant variants of HIV-1 with mutations in PR could not be inhibited sufficiently with PRIs that are currently available in clinical practice. Efficient yet temporary suppression of viral replication was achieved by a lopinavir (LPV) treatment.
Keywords: RNA virová; Amino Acid Substitution; Humans; Antiretroviral Therapy, Highly Active; Anti-HIV Agents; HIV-proteasa; CD4 Lymphocyte Count; HIV Protease Inhibitors; Disease Progression; HIV infekce; HIV Reverse Transcriptase; HIV Infections; Reverse Transcriptase Inhibitors; Female; HIV reverzní transkriptasa; mutace; Viral Load; polymerázová řetězová reakce s reverzní transkripcí; Genotype; lidé; Reverse Transcriptase Polymerase Chain Reaction; HIV Protease; inhibitory reverzní transkriptasy; virová nálož; virová léková rezistence; počet CD4 lymfocytů; ženské pohlaví; Male; substituce aminokyselin; Czech Republic; vysoce aktivní antiretrovirová terapie; Drug Resistance, Viral; látky proti HIV; inhibitory HIV-proteasy; RNA, Viral; genotyp; progrese nemoci; Mutation; Česká republika; mužské pohlaví; HIV-1